1993
DOI: 10.1002/jlb.54.5.430
|View full text |Cite
|
Sign up to set email alerts
|

Preincubation with anti-CD4 influences activation of human T cells by subsequent co-cross-linking of CD4 with CD3

Abstract: Under physiological conditions, T cell activation by major histocompatibility complex (MHC)-antigen complexes requires engagement of both the T cell receptor (TcR) and the CD4 (or CD8) accessory molecules. It has been shown, however, that ligation of CD4 and CD8 can also inhibit T cell activation in an MHC-independent way. Therefore, the role of CD4 in T cell activation and the mechanism of the suppression of T cell functions by anti-CD4 are as yet unclear. We activated T cells by CD4/CD3 co-cross-linking and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…A discrepancy between our data and the study by San Luis et al 20 lies probably in the nature of T cells used; in the current study, they were freshly isolated from MLNs, whereas in San Luis et al 20 they were isolated from the spleen and expanded using stimulation with anti‐CD3 and IL‐2 before experiments. T‐cell preactivation in the course of such expansion may facilitate T‐cell responses to CD3 stimulation, including PTK‐mediated signaling and proliferation 92 , 93 , 94…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A discrepancy between our data and the study by San Luis et al 20 lies probably in the nature of T cells used; in the current study, they were freshly isolated from MLNs, whereas in San Luis et al 20 they were isolated from the spleen and expanded using stimulation with anti‐CD3 and IL‐2 before experiments. T‐cell preactivation in the course of such expansion may facilitate T‐cell responses to CD3 stimulation, including PTK‐mediated signaling and proliferation 92 , 93 , 94…”
Section: Discussionmentioning
confidence: 99%
“…T-cell preactivation in the course of such expansion may facilitate T-cell responses to CD3 stimulation, including PTK-mediated signaling and proliferation. [92][93][94] Augmentation of CD3-mediated signaling in MLN CD4 þ T cells from WT and KO mice may also be linked to T-cell preactivation, as TNBS is thought to cause colitis by haptenating antigens, thus generating a strong TCR/CD3-mediated stimulus, 33 which activates MLN CD4 þ T cells in TNBS-treated mice. The ability of TNBS treatment to facilitate signaling in MLN T cells from TULA and TULA-2 sKO mice correlates well with the effects of TNBS treatment on colitis in these mice and on in vitro cytokine production by TULA-2 sKO T cells, as it is expected.…”
Section: Discussionmentioning
confidence: 99%
“…In early studies, anti-CD4 mAbs were found capable to induce either cell depletion [26] or functional inactivation of T cells [27,28], although activation of T-cell functions was also reported[29]. These divergent effects may explain the inconsistency in the clinical efficacy of different anti-CD4 mAbs particularly in the treatment of rheumatoid arthritis, namely a promising initial efficacy in open anti-CD4 trials [30,31], subsequent discouraging double-blind clinical trials (reviewed in [32]), and, finally, a revitalization of the anti-CD4 treatment notion with new, humanized anti-CD4 mAbs [33].…”
Section: ) Anti-cd4 Antibodies In Clinical Practice: Beyond Immune Smentioning
confidence: 99%
“…gp120 binding to CD4 in CEM cells induces CD4-p561rk dissociation and inhibition of CD4-linked p56lCk activity, and dissociation of p56lck from CD4 was shown to be a prerequisite for the decrease of membrane CD4 expression [34]. Moreover, others have demonstrated that pretreatment of T cells with anti-CD4 mAb inhibited CD3-mediated calcium influx [35] and T cell proliferation [36]. Taken together, these results strongly suggest that a close contact between the CD4-p56lCk and the CD3-TcR complexes is necessary for efficient signal transduction.…”
Section: Introductionmentioning
confidence: 98%